Quantitative Bio-Imaging Tools to Dissect the Interplay of Membrane and Cytoskeletal Actin Dynamics in Immune Cells - Schneider, Falk; Colin-York, Huw; Fritzsche, Marco (Frontiers in Immunology, 2021)
Cellular function is reliant on the dynamic interplay between the plasma membrane and the actin cytoskeleton. This critical relationship is of particular importance in immune cells, where both the cytoskeleton and the plasma membrane work in concert to organise and potentiate immune signalling events. Despite their importance, there remains a critical gap in understanding how these respective dynamics are coupled, and how this coupling in turn may influence immune cell function from the bottom up. In this review, we highlight recent optical technologies that could provide strategies to investigate the simultaneous dynamics of both the cytoskeleton and membrane as well as their interplay, focusing on current and future applications in immune cells. We provide a guide of the spatio-temporal scale of each technique as well as highlighting novel probes and labels that have the potential to provide insights into membrane and cytoskeletal dynamics. The quantitative biophysical tools presented here provide a new and exciting route to uncover the relationship between plasma membrane and cytoskeletal dynamics that underlies immune cell function.